A morphometric ultrastructural study of the seminal vesicle of rats submitted to experimental chronic alcoholism - Martinez, F. E.; Garcia, P. J.; Padovani, C. R.; Cagnon, VHA; Martinez, M. (Editrice Compositori Bologna, 1997)
The effects of chronic alcohol ingestion on the secretory epithelium of the seminal vesicle were studied in rats (Rattus norvegicus). Male adult albino Wistar rats were divided into two groups: alcoholic and control. Tips of the seminal vesicle were removed and prepared for light and electron microscopy. Ultrastructural observations on the epithelial cells of the seminal vesicle showed reduced epithelial cell size, decreased apical secretory vacuoles, irregularly shaped nuclei with deep infoldings, increased lipid droplets and dense bodies, a small number of microvilli covering the cell surface, and signs of degeneration. In addition to the hormonal effects, alcohol may act on the secretory epithelium of the seminal vesicle.
Keywords: alcohol; accessory sexual glands; seminal vesicle; histology; ultrastructure